A beregszászi járás népességföldrajzi adottságai - Fodor Gyula; Фодор Дюло (Didakt Kft., 2005)
Abstract. The Beregszász district is one of the thirteen districts of the Transcarpathian region. It is situated on the southwestern part of the region, bordering on the Ungvár, Munkács, Nagyszőlős, Ilosva districts and the Republic of Hungary. Its area is 720 square kilometres and its population is about 80,3 thousand. The district is mostly inhabited by Hungarians, who make up three-fourth of its population, and Ukrainians (almost 20 percent). The Hungarians mostly live in the rural areas, while the Ukrainians inhabit the town of Beregszász and a couple of villages in the western and southern part of the district. As for the age structure of the district’s population, it’s gradually growing older, because the number of births is diminishing every year, while the life span of the people is on the constant increase. The reproduction of the population is of minus sign, which means that the district’s population decreases quickly enough. One more negative process is that the balance of migration also shows an increasing deficit, mainly in the case of the Hungarian population.
Демографічна характеристика Берегівського району
https://opac3.brff.monguz.hu:443/hu/record/-/record/160863
Keywords: Beregszász district; ethnic structure; migration; population Geography